Short interpregnancy intervals and adverse maternal outcomes in high‐resource settings: An updated systematic review. Issue 1 (12th October 2018) - Hutcheon, Jennifer A.; Nelson, Heidi D.; Stidd, Reva; Moskosky, Susan; Ahrens, Katherine A.
Abstract: Background: Currently, no federal guidelines provide recommendations on healthy birth spacing for women in the United States. This systematic review summarises associations between short interpregnancy intervals and adverse maternal outcomes to inform the development of birth spacing recommendations for the United States. Methods: PubMed/Medline, POPLINE, EMBASE, CINAHL, the Cochrane Database of Systematic Reviews, and a previous systematic review were searched to identify relevant articles published from 1 January 2006 and 1 May 2017. Included studies reported maternal health outcomes following a short versus longer interpregnancy interval, were conducted in high‐resource settings, and adjusted estimates for at least maternal age. Two investigators independently assessed study quality and applicability using established methods. Results: Seven cohort studies met inclusion criteria. There was limited but consistent evidence that short interpregnancy interval is associated with increased risk of precipitous labour and decreased risks of labour dystocia. There was some evidence that short interpregnancy interval is associated with increased risks of subsequent pre‐pregnancy obesity and gestational diabetes, and decreased risk of preeclampsia. Among women with a previous caesarean delivery, short interpregnancy interval was associated with increased risk of uterine rupture in one study. No studies reported outcomes related to maternal depression, interpregnancy weight gain, maternal anaemia, or maternal mortality. Conclusions: In studies from high‐resource settings, short interpregnancy intervals are associated with both increased and decreased risks of adverse maternal outcomes. However, most outcomes were evaluated in single studies, and the strength of evidence supporting associations is low.